Pick up justice in a civil law dispute: between culture and justice - Suparman, Eman (Opción, 2019)
This article aims to analyze the forms of justice in civil disputes between legal cultures and bureaucratic justice in Indonesia via comparative qualitative research methods. As a result, the court institution has proven unable to meet the expectations of justice seekers. Many factors did cause the court in its history to be like that. The conclusion of this article is that there are indications that judges do not have enough courage to make decisions that are different from the normative provisions of the law so that substantial justice is always difficult to materialize through judges' decisions.